Manufacturing method of graphite anode for rare earth electrolytic cell
By detecting and processing unqualified products during the preparation of graphite anode, and plating graphene conductive film on the surface of the anode rod, the problem of unqualified products in the preparation of traditional graphite anode is solved, the production efficiency and electrolytic efficiency are improved, and the cost is reduced.
Patent Information
- Application Number
- CN202411755243.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-03
- Publication Date
- 2025-03-11
AI Technical Summary
Traditional graphite anodes are prone to unqualified products during the preparation process, and discarding them directly will increase the preparation cost.
The method of placing anode solution, preparing anode rod, detecting unqualified products and processing them in a graphite furnace to convert them into qualified products, and plating graphene conductive film on the surface of the anode rod.
The production pass rate of graphite anode rod is improved, the preparation cost is reduced, the electrolytic efficiency is improved, unnecessary power consumption is reduced, and the preparation process is simplified and the yield is improved.
Smart Images

Figure CN119591403A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of rare earth electrolytic cells, in particular to a method for manufacturing a graphite anode for a rare earth electrolytic cell. Background Art
[0002] Rare earth electrolytic cells are the main equipment for producing rare earth metals and their alloys by molten salt electrolysis. The quality of their performance directly affects the production efficiency and cost of rare earth metals. In recent years, with the rapid development of the rare earth industry, rare earth electrolytic cell technology has also made significant progress. Its main structure includes components such as the cell body, electrodes, electrolyte circulation system and control system. In production, the main function of the rare earth electrolytic cell is to separate rare earth elements through electrochemical reactions to obtain high-purity rare earth metals or compounds.
[0003] The graphite anode is one of the components of the rare earth electrolyzer. Graphite itself has a stable structure, is relatively safe, and is inexpensive. Therefore, graphite is widely used as an anode in rare earth electrolyzers. Compared with other materials, graphite is more reliable in safety and is not easily affected by factors such as overcharging and over-discharging. Therefore, it has a good performance in the safety of rare earth electrolyzers. In addition, graphite has good capacity stability, a long service life, and is not easy to lose its electrochemical ability.
[0004] However, traditional graphite anodes have the following disadvantages:
[0005] Traditional graphite anodes are prone to producing unqualified products during the preparation process. If the unqualified products are directly discarded, the preparation cost of the graphite anode will be greatly increased. Summary of the invention
[0006] The purpose of the present invention is to provide a method for manufacturing a graphite anode for a rare earth electrolytic cell, so as to solve the problem that unqualified products are easily produced during the preparation process of traditional graphite anodes proposed in the above background technology. If the unqualified products are directly discarded, the preparation cost of the graphite anode is greatly increased.
[0007] To achieve the above object, the present invention provides the following technical solution: a method for manufacturing a graphite anode for a rare earth electrolytic cell, comprising the following steps:
[0008] Step 1: Prepare the anode solution: When the graphite sheet is added to the chemical solution, it is prepared into the anode solution through a series of processing;
[0009] Step 2: Prepare the anode rod: put the prepared anode solution into the anode rod mold for drying and shaping, and demould after natural cooling;
[0010] Step 3: Product testing: The prepared anode rods are tested by ultrasonic flaw detection equipment, and unqualified anode rods are placed in a graphite furnace for treatment and converted into qualified anode rods;
[0011] Step 4: Product coating: Use an electron beam evaporator to coat several layers of graphene conductive film on the surface of the metal electrode in an alternating manner on the surface of the graphite rod.
[0012] As a preferred technical solution of the present invention, the graphite sheets in step 1 include natural graphite aggregates, synthetic graphite aggregates, expanded graphite aggregates, highly oriented pyrolytic graphite and graphite fibers.
[0013] As a preferred technical solution of the present invention, the specific process of a series of processing in the step 1 is as follows: S1, graphite sheet expansion: by using ammonium persulfate and 98% concentrated sulfuric acid to mix with graphite sheets in a certain proportion and standing for a period of time to expand the graphite sheets; S2, the first oxidation of graphite sheets: after the expansion of the graphite sheets, 98% concentrated sulfuric acid and potassium permanganate are added at a temperature of 30-60°C, the reaction time is 4h, and the first oxidation is carried out; S3, the second oxidation of graphite sheets: after the first oxidation, pour it into deionized water with a volume twice that of sulfuric acid, and carry out the second oxidation at 70-90°C, the reaction time is 0.5-8h; S4, product filtration: the reaction product after the secondary oxidation is poured into a 400 mesh screen for filtration; S5, alkali solution addition: the pre-oxidized graphite obtained after filtration is placed in a sodium hydroxide solution to adjust the pH to 10-14 to obtain solution A; S6, stabilizing the pH: TrisHcl buffer is added dropwise to solution A to stabilize the pH.
[0014] As a preferred technical solution of the present invention, the radius of the anode rod prepared by the anode rod mold in step 2 is 100 mm.
[0015] As a preferred technical solution of the present invention, the processing in step three is specifically to connect the unqualified products in series in the graphite furnace and wrap the connected unqualified products with fillers, and then conduct electric processing under the condition that the gas in the graphite furnace is extracted by a vacuum pump.
[0016] As a preferred technical solution of the present invention, the power-on time is 1015 hours, the unqualified anode rod is powered on to generate heat, so that the temperature in the furnace gradually rises from room temperature to 2200-3000°C, and a qualified anode rod is obtained after cooling.
[0017] As a preferred technical solution of the present invention, the filler is specifically calcined coke particles.
[0018] As a preferred technical solution of the present invention, the number of layers of the graphene conductive film in step 4 is specifically that the number of layers of the graphene conductive film is ≥ 2.
[0019] As a preferred technical solution of the present invention, the vacuum degree in the electron beam evaporation chamber in step 4 is controlled at 10 -7 -10 -4 Pa, substrate temperature is controlled at 100-500℃.
[0020] Compared with the prior art, the present invention has the following beneficial effects:
[0021] 1. The unqualified products are placed in a graphite furnace for processing, effectively removing the burnt acne on the surface of the unqualified anode products, as well as the residual protrusions and impurities of the internal transverse cracks, so as to transform them into qualified graphite anode rods, improve the qualified rate of graphite anode rod production, and reduce the preparation cost of graphite anodes;
[0022] 2. The surface of the prepared anode rod is adhered with a smooth graphene film, and the surface porosity of the prepared graphite anode rod is uniform, which improves the electrical efficiency of the graphite anode rod electrolysis, reduces unnecessary power consumption, and reduces costs;
[0023] 3. The entire anode solution preparation process is shortened by 12-36 hours compared to the ordinary ball milling method, and the yield can reach 100%, which greatly improves the preparation efficiency and the yield, and is more conducive to industrial large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 is a flow chart of the present invention;
[0025] Figure 2 A flow chart for configuring the anode solution for the present invention;
[0026] Figure 3 is a schematic diagram of the structure of the graphite sheet of the present invention;
[0027] Figure 4 The distance diagram of the graphite anode from the bottom of the rare earth electrolytic cell of the present invention;
[0028] Figure 5 The graph is a gas content curve of the graphite anode of the present invention at different insertion depths;
[0029] Figure 6 It is a cross-sectional view of the rare earth electrolytic cell of the present invention. DETAILED DESCRIPTION
[0030] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0031] See also Figure 1-6 The present invention provides a method for manufacturing a graphite anode for a rare earth electrolytic cell, comprising the following steps:
[0032] Step 1: Prepare the anode solution: When the graphite sheet is added to the chemical solution, it is prepared into the anode solution through a series of processing;
[0033] Step 2: Prepare the anode rod: put the prepared anode solution into the anode rod mold for drying and shaping, and demould after natural cooling;
[0034] Step 3: Product testing: The prepared anode rods are tested by ultrasonic flaw detection equipment, and unqualified anode rods are placed in a graphite furnace for treatment and converted into qualified anode rods;
[0035] Step 4: Product coating: Use an electron beam evaporator to coat several layers of graphene conductive film on the surface of the metal electrode in an alternating manner on the surface of the graphite rod.
[0036] In step 1, the graphite sheets include natural graphite aggregates, synthetic graphite aggregates, expanded graphite aggregates, highly oriented pyrolytic graphite and graphite fibers.
[0037] The specific process of a series of processing in step one is as follows: S1, graphite sheet expansion: the graphite sheet is expanded by mixing ammonium persulfate and 98% concentrated sulfuric acid with the graphite sheet in a certain proportion and standing for a period of time; S2, the first oxidation of the graphite sheet: after the graphite sheet is expanded, 98% concentrated sulfuric acid and potassium permanganate are added at a temperature of 30-60°C and the reaction time is 4h to carry out the first oxidation; S3, the second oxidation of the graphite sheet: after the first oxidation, pour it into deionized water with a volume twice that of sulfuric acid, and carry out the second oxidation at 70-90°C and the reaction time is 0.5-8h; S4, product filtration: the reaction product after the secondary oxidation is poured into a 400-mesh sieve for filtration; S5, alkali solution addition: the pre-oxidized graphite obtained after filtration is placed in a sodium hydroxide solution to adjust the pH to 10-14 to obtain solution A; S6, stabilizing the pH: TrisHcl buffer solution is added dropwise to solution A to stabilize the pH.
[0038] In step 2, the radius of the anode rod prepared by the anode rod mold is 100 mm.
[0039] The processing in step three is specifically to connect the unqualified products in series in the graphite furnace and wrap the connected unqualified products with fillers, and then conduct electric processing under the condition that the gas in the graphite furnace is extracted by a vacuum pump.
[0040] The power-on time is 1015 hours. The unqualified anode rods are powered on to generate heat, causing the temperature in the furnace to gradually rise from room temperature to 2200-3000℃. After cooling, qualified anode rods are obtained.
[0041] The filler is specifically calcined coke particles.
[0042] In step 4, the number of layers of the graphene conductive film is specifically that the number of layers of the graphene conductive film is ≥ 2 layers.
[0043] In step 4, the vacuum degree in the electron beam evaporation chamber is controlled at 10 -7 -10 -4 Pa, substrate temperature is controlled at 100-500℃.
[0044] Embodiment 1:
[0045] In the present invention, ammonium persulfate and 98% concentrated sulfuric acid are mixed with graphite sheets in a certain proportion and left to stand for a period of time to expand the graphite sheets. The graphite sheets are made of the following components: by weight: 10 parts of natural graphite aggregates, 30 parts of synthetic graphite aggregates, 20 parts of expanded graphite aggregates, 10 parts of highly oriented pyrolytic graphite and 30 parts of graphite fibers. After the graphite sheets are expanded, 98% concentrated sulfuric acid and potassium permanganate are added at a temperature of 30-60° C. for a reaction time of 4 hours to perform a first oxidation. After the first oxidation, deionized water with a volume twice that of sulfuric acid is poured into the solution, and a second oxidation is performed at 70-90° C. for a reaction time of 0.5-8 hours. The reaction product after the second oxidation is poured into a 400-mesh screen for filtration. The pre-oxidized graphite obtained after filtration is placed in a sodium hydroxide solution to adjust the pH to 10-14 to obtain a solution A. Trichloride is added dropwise into the solution A. sHcl buffer is used to stabilize the pH to obtain the required anode solution; the entire preparation process is simplified, and even the ball milling time is shortened by 12-36 hours compared with the ordinary ball milling method, and the yield can reach 100%, which greatly improves the preparation efficiency and the yield, and is more conducive to the realization of industrial large-scale production. The prepared anode solution is placed in the anode rod mold for drying and shaping, and demolded after natural cooling, and the radius of the prepared anode rod is 100mm; the prepared anode rod is tested by ultrasonic flaw detection equipment, and the unqualified anode rod is placed in a graphite furnace for treatment to be converted into a qualified anode rod, and the unqualified products are connected in series in the graphite furnace and wrapped around the connected unqualified products with fillers, and then the gas in the graphite furnace is extracted by a vacuum pump and electrified for processing; an electron beam evaporator is used to alternately coat a plurality of layers of graphene conductive film on the surface of the graphite rod on the surface of the metal electrode, and the vacuum degree in the cavity of the electron beam evaporator is controlled at 10 -7 -10 -4 Pa and the substrate temperature are controlled at 100-500° C. to obtain a large-area, layered, and flat-surface graphite anode. Moreover, the obtained graphite anode material has the advantages of high capacitance and high coulomb efficiency.
[0046] The unqualified products are placed in a graphite furnace for pretreatment to effectively remove the burnt acne on the surface of the unqualified anode products, as well as the residual protrusions and impurities of the internal transverse cracks, which is conducive to graphitization to improve the true density and compressive strength;
[0047] The pore size of the anode material surface used on site is 20-200um, but the uniformity of the voids in the electrode material is poor, and the results obtained by sampling and measurement vary greatly, with the maximum difference being about 180um. In the production process, the unevenness of the material will increase the difficulty of controlling the production process parameters, resulting in increased equipment loss, especially for electrolytic production. The control of the internal temperature of the tank body mainly depends on the control of the voltage between the two electrodes, and the selection of electrode materials will affect the tank body voltage. The change in the internal temperature distribution of the tank body and the voltage of the reduced anode and cathode can be divided into equilibrium voltage, cathode and anode concentration overvoltage, ohmic overvoltage, and anode and cathode activation overvoltage. The generation of anode gas mainly depends on the nucleation and growth of pores on the anode surface at the junction with the molten salt. The presence of these pores accelerates the oxidation rate of the electrode, and the oxidation rate of carbon is proportional to the porosity. Therefore, the surface of the prepared anode rod adheres to a smooth graphene film, and the surface porosity of the prepared graphite anode rod is uniform, which improves the electrical efficiency of the graphite anode rod electrolysis, reduces unnecessary power consumption, and reduces costs.
[0048] In conjunction with the instruction manual Figure 6 This is a schematic diagram of the structure of a rare earth electrolyzer. Natural graphite aggregates have low cost, high specific capacity and compaction density. Synthetic graphite aggregates have high strength, high temperature stability, low friction coefficient and corrosion resistance. Expanded graphite aggregates have light weight and heat insulation properties. Highly oriented pyrolytic graphite is a "crystalline" graphite with good crystal structure, strong preferential orientation and high degree of graphitization. Graphite fiber has excellent electrical conductivity, and the prepared anode solution has good electrical conductivity.
[0049] In conjunction with the instruction manual Figure 4The graph is a gas content curve of a graphite anode rod inserted into a rare earth electrolytic cell at a distance of 250mm from the bottom. When the radius of the graphite anode rod is less than 75mm, the anode gas is affected by the rare earth electrolytic cell type, which may affect the wettability of the electrode and cause secondary chemical reactions. At the same time, the lower part of the molten salt does not flow smoothly, which is not conducive to the recycling of the electrolyte. When the radius of the graphite anode rod is greater than 120mm, the current density on the electrode will decrease, the resistance between the electrodes will increase, the power consumption of the cell will increase, and the stirring effect of the gas on the fluid in the cell will decrease, which is not conducive to electrolysis. Therefore, the radius of the appropriate graphite anode rod is 100mm. Specifically, when the radius of the inner surface of the anode is less than 75mm, the gas cannot diffuse freely due to the influence of the cell type, and the gas is relatively concentrated. The gas moves upward under the action of buoyancy, and the distance between the cathode and cathode is reduced, which also reduces the cross-sectional area of the cell. The reaction force on the fluid accelerates the movement of the fluid , the resistance of gas overflow is reduced, which speeds up the gas rising speed, and the gas content is not high. However, the movement of molten salt is fast, which causes resistance to the metal precipitation generated at the cathode. At the same time, the anode gas is easy to contact with the metal obtained by reduction, causing secondary chemical reactions and reducing production efficiency. When the radius of the inner surface of the anode is greater than 120mm, - on the one hand, the lateral diffusion range of the gas is increased. Under the same cell voltage, the current density of the electrode is reduced, the gas generation rate is reduced, the gas content is reduced, and the force of the gas on the fluid is reduced, which is not conducive to the full movement of the fluid. The floating resistance of the bubble is increased, and the aggregation of bubbles will hinder the full contact between the molten salt and the electrode, making the electrolysis of the rare earth electrolytic cell electrolysis system with poor wettability more difficult, and even affecting the normal progress of the electrolysis process. Taking comprehensive considerations, while ensuring the normal progress of electrolysis and improving production efficiency as much as possible, the inner diameter of the anode is preferably about 100mm;
[0050] In conjunction with the instruction manual Figure 5 The graph is a gas content curve at different insertion depths 50mm away from the central symmetry axis. When the insertion depth of the graphite anode rod is less than 190mm, the fluid flow in the cell is slow and the electrolysis efficiency is low. When the insertion depth of the graphite anode rod is greater than 250mm, the gas content in the cell will increase, increasing the probability of secondary chemical reactions, which is not conducive to production. After simulation research, the insertion depth of the graphite anode rod in the rare earth electrolytic cell should be 215-225mm.
[0051] Embodiment 2:
[0052] In the present invention, ammonium persulfate and 98% concentrated sulfuric acid are mixed with graphite sheets in a certain proportion and left to stand for a period of time to expand the graphite sheets. The graphite sheets include the following components: by weight: 20 parts of natural graphite aggregates, 20 parts of synthetic graphite aggregates, 20 parts of expanded graphite aggregates, 20 parts of highly oriented pyrolytic graphite and 20 parts of graphite fibers. After the graphite sheet is expanded, 98% concentrated sulfuric acid and potassium permanganate are added at a temperature of 30-60°C for a reaction time of 4 hours to carry out the first oxidation; after the first oxidation, deionized water with a volume twice that of the sulfuric acid is poured into the solution, and the second oxidation is carried out at 70-90°C for a reaction time of 0.5-8 hours, and the reaction product after the second oxidation is poured into a 400-mesh sieve for filtration, and the pre-oxidized graphite obtained after filtration is placed in a potassium hydroxide solution to adjust the pH to 10-14 to obtain a solution A, and TrisHcl buffer is added dropwise into the solution A to stabilize the pH to obtain the desired anode solution; the entire preparation process is simplified, and even the ball milling time is shortened by 12-36 hours compared with the ordinary ball milling method, and the yield can be The anode rod has a radius of 100 mm. The anode rod is tested by ultrasonic flaw detection equipment, and unqualified anode rods are placed in a graphite furnace for treatment to be converted into qualified anode rods. Unqualified products are connected in series in the graphite furnace and wrapped around with fillers. Then, the gas in the graphite furnace is extracted by a vacuum pump and the processing is carried out under the condition of electrification. Electron beam evaporation machine is used to alternately coat several layers of graphene conductive film on the surface of the graphite rod on the surface of the metal electrode. The vacuum degree in the cavity of the electron beam evaporation machine is controlled at 10 -7 -10 -4 Pa and the substrate temperature are controlled at 100-500° C. to obtain a large-area, layered, and flat-surface graphite anode. Moreover, the obtained graphite anode material has the advantages of high capacitance and high coulomb efficiency.
[0053] Embodiment 3:
[0054] In the present invention, ammonium persulfate and 98% concentrated sulfuric acid are mixed with graphite sheets in a certain proportion and left to stand for a period of time to expand the graphite sheets. The graphite sheets are made of the following components: by weight: 25 parts of natural graphite aggregates, 15 parts of synthetic graphite aggregates, 10 parts of expanded graphite aggregates, 30 parts of highly oriented pyrolytic graphite and 20 parts of graphite fibers. After the graphite sheets are expanded, 98% concentrated sulfuric acid and potassium permanganate are added at a temperature of 30-60° C. for a reaction time of 4 hours to perform a first oxidation. After the first oxidation, deionized water with a volume twice that of sulfuric acid is poured into the solution, and a second oxidation is performed at a temperature of 70-90° C. for a reaction time of 0.5-8 hours. The reaction product after the second oxidation is poured into a 400-mesh screen for filtration. The pre-oxidized graphite obtained after filtration is placed in a potassium hydroxide solution to adjust the pH to 10-14 to obtain a solution A. Trichloride is added dropwise into the solution A. sHcl buffer is used to stabilize the pH to obtain the required anode solution; the entire preparation process is simplified, and even the ball milling time is shortened by 12-36 hours compared with the ordinary ball milling method, and the yield can reach 100%, which greatly improves the preparation efficiency and the yield, and is more conducive to the realization of industrial large-scale production. The prepared anode solution is placed in the anode rod mold for drying and shaping, and demolded after natural cooling, and the radius of the prepared anode rod is 100mm; the prepared anode rod is tested by ultrasonic flaw detection equipment, and the unqualified anode rod is placed in a graphite furnace for treatment to be converted into a qualified anode rod, and the unqualified products are connected in series in the graphite furnace and wrapped around the connected unqualified products with fillers, and then the gas in the graphite furnace is extracted by a vacuum pump and electrified for processing; an electron beam evaporator is used to alternately coat a plurality of layers of graphene conductive film on the surface of the graphite rod on the surface of the metal electrode, and the vacuum degree in the cavity of the electron beam evaporator is controlled at 10 -7 -10 -4 Pa and the substrate temperature are controlled at 100-500° C. to obtain a large-area, layered, and flat-surface graphite anode. Moreover, the obtained graphite anode material has the advantages of high capacitance and high coulomb efficiency.
[0055] Embodiment 4:
[0056] In the present invention, ammonium persulfate and 98% concentrated sulfuric acid are mixed with graphite sheets in a certain proportion and left to stand for a period of time to expand the graphite sheets. The graphite sheets are made of the following components: by weight: 22 parts of natural graphite aggregates, 28 parts of synthetic graphite aggregates, 20 parts of expanded graphite aggregates, 14 parts of highly oriented pyrolytic graphite and 16 parts of graphite fibers. After the graphite sheets are expanded, 98% concentrated sulfuric acid and potassium permanganate are added at a temperature of 30-60° C. for a reaction time of 4 hours to perform a first oxidation. After the first oxidation, deionized water with a volume twice that of sulfuric acid is poured into the solution, and a second oxidation is performed at a temperature of 70-90° C. for a reaction time of 0.5-8 hours. The reaction product after the second oxidation is poured into a 400-mesh screen for filtration. The pre-oxidized graphite obtained after filtration is placed in a sodium hydroxide solution to adjust the pH to 10-14 to obtain a solution A. Trichloride is added dropwise into the solution A. sHcl buffer is used to stabilize the pH to obtain the required anode solution; the entire preparation process is simplified, and even the ball milling time is shortened by 12-36 hours compared with the ordinary ball milling method, and the yield can reach 100%, which greatly improves the preparation efficiency and the yield, and is more conducive to the realization of industrial large-scale production. The prepared anode solution is placed in the anode rod mold for drying and shaping, and demolded after natural cooling, and the radius of the prepared anode rod is 100mm; the prepared anode rod is tested by ultrasonic flaw detection equipment, and the unqualified anode rod is placed in a graphite furnace for treatment to be converted into a qualified anode rod, and the unqualified products are connected in series in the graphite furnace and wrapped around the connected unqualified products with fillers, and then the gas in the graphite furnace is extracted by a vacuum pump and electrified for processing; an electron beam evaporator is used to alternately coat a plurality of layers of graphene conductive film on the surface of the graphite rod on the surface of the metal electrode, and the vacuum degree in the cavity of the electron beam evaporator is controlled at 10 -7 -10 -4 Pa and the substrate temperature are controlled at 100-500° C. to obtain a large-area, layered, and flat-surface graphite anode. Moreover, the obtained graphite anode material has the advantages of high capacitance and high coulomb efficiency.
[0057] Embodiment 5:
[0058] In the present invention, ammonium persulfate and 98% concentrated sulfuric acid are mixed with graphite sheets in a certain proportion and left to stand for a period of time to expand the graphite sheets. The graphite sheets are made of the following components: by weight: 18 parts of natural graphite aggregates, 22 parts of synthetic graphite aggregates, 20 parts of expanded graphite aggregates, 12 parts of highly oriented pyrolytic graphite and 38 parts of graphite fibers. After the graphite sheets are expanded, 98% concentrated sulfuric acid and potassium permanganate are added at a temperature of 30-60° C. for a reaction time of 4 hours to perform a first oxidation. After the first oxidation, deionized water with a volume twice that of sulfuric acid is poured into the solution, and a second oxidation is performed at 70-90° C. for a reaction time of 0.5-8 hours. The reaction product after the second oxidation is poured into a 400-mesh screen for filtration. The pre-oxidized graphite obtained after filtration is placed in a sodium hydroxide solution to adjust the pH to 10-14 to obtain a solution A. Trichloride is added dropwise into the solution A. sHcl buffer is used to stabilize the pH to obtain the required anode solution; the entire preparation process is simplified, and even the ball milling time is shortened by 12-36 hours compared with the ordinary ball milling method, and the yield can reach 100%, which greatly improves the preparation efficiency and the yield, and is more conducive to the realization of industrial large-scale production. The prepared anode solution is placed in the anode rod mold for drying and shaping, and demolded after natural cooling, and the radius of the prepared anode rod is 100mm; the prepared anode rod is tested by ultrasonic flaw detection equipment, and the unqualified anode rod is placed in a graphite furnace for treatment to be converted into a qualified anode rod, and the unqualified products are connected in series in the graphite furnace and wrapped around the connected unqualified products with fillers, and then the gas in the graphite furnace is extracted by a vacuum pump and electrified for processing; an electron beam evaporator is used to alternately coat a plurality of layers of graphene conductive film on the surface of the graphite rod on the surface of the metal electrode, and the vacuum degree in the cavity of the electron beam evaporator is controlled at 10 -7 -10 -4 Pa and the substrate temperature are controlled at 100-500° C. to obtain a large-area, layered, and flat-surface graphite anode. Moreover, the obtained graphite anode material has the advantages of high capacitance and high coulomb efficiency.
[0059] Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for those skilled in the art to modify the technical solutions described in the aforementioned embodiments, or to make equivalent substitutions for some of the technical features therein. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for manufacturing a graphite anode for a rare earth electrolytic cell, characterized in that: The following steps are involved: Step 1: Prepare the anode solution: When the graphite sheet is added to the chemical solution, it is prepared into the anode solution through a series of processing; Step 2: Prepare the anode rod: put the prepared anode solution into the anode rod mold for drying and shaping, and demould after natural cooling; Step 3: Product testing: The prepared anode rods are tested by ultrasonic flaw detection equipment, and unqualified anode rods are placed in a graphite furnace for treatment and converted into qualified anode rods; Step 4: Product coating: Use an electron beam evaporator to coat several layers of graphene conductive film on the surface of the metal electrode in an alternating manner on the surface of the graphite rod.
2. The method for manufacturing a graphite anode for a rare earth electrolytic cell according to claim 1, characterized in that: The graphite sheets in step 1 include natural graphite aggregates, synthetic graphite aggregates, expanded graphite aggregates, highly oriented pyrolytic graphite and graphite fibers.
3. The method for manufacturing a graphite anode for a rare earth electrolytic cell according to claim 1, characterized in that: The specific process of a series of processing in the step 1 is as follows: S1, graphite sheet expansion: the graphite sheet is expanded by mixing ammonium persulfate and 98% concentrated sulfuric acid with the graphite sheet in a certain proportion and standing for a period of time; S2, the first oxidation of the graphite sheet: after the graphite sheet is expanded, 98% concentrated sulfuric acid and potassium permanganate are added at a temperature of 30-60° C. and the reaction time is 4 hours to carry out the first oxidation; S3, the second oxidation of the graphite sheet: after the first oxidation, the graphite sheet is poured into deionized water with a volume twice that of sulfuric acid, and the second oxidation is carried out at 70-90° C. and the reaction time is 0.5-8 hours; S4, product filtration: the reaction product after the second oxidation is poured into a 400 mesh sieve for filtration; S5, alkali solution addition: the pre-oxidized graphite obtained after filtration is placed in a sodium hydroxide solution to adjust the pH to 10-14 to obtain solution A; S6, stabilizing the pH: TrisHcl buffer solution is added dropwise to solution A to stabilize the pH.
4. The method for manufacturing a graphite anode for a rare earth electrolytic cell according to claim 1, characterized in that: The radius of the anode rod produced by the anode rod mold in step 2 is 100 mm.
5. The method for manufacturing a graphite anode for a rare earth electrolytic cell according to claim 1, characterized in that: The processing in step three is specifically to connect the unqualified products in series in the graphite furnace and wrap the connected unqualified products with fillers, and then conduct electrical processing under the condition that the gas in the graphite furnace is extracted by a vacuum pump.
6. The method for manufacturing a graphite anode for a rare earth electrolytic cell according to claim 5, characterized in that: The power-on time is 1015 hours. The unqualified anode rod is powered on to generate heat, so that the temperature in the furnace gradually rises from room temperature to 2200-3000°C, and a qualified anode rod is obtained after cooling.
7. The method for manufacturing a graphite anode for a rare earth electrolytic cell according to claim 5, characterized in that: The filler is specifically calcined coke particles.
8. The method for manufacturing a graphite anode for a rare earth electrolytic cell according to claim 1, characterized in that: In the step 4, the number of layers of the graphene conductive film is specifically that the number of layers of the graphene conductive film is ≥ 2.
9. The method for manufacturing a graphite anode for a rare earth electrolytic cell according to claim 1, characterized in that: In the fourth step, the vacuum degree in the electron beam evaporation chamber is controlled at 10 -7 -10 -4 Pa, substrate temperature is controlled at 100-500℃.